Advances in Cryogenic Engineering 2000
DOI: 10.1007/978-1-4615-4215-5_44
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Large Helium Cryogenic Systems: Experience from Recent Projects at CERN

Abstract: Large projects based on applied superconductivity, such as particle accelerators, tokamaks or SMES, require powerful and complex helium cryogenic systems, the cost of which represents a significant, if not dominant fraction of the total capital and operational expenditure. It is therefore important to establish guidelines and scaling laws for costing such systems, based on synthetic estimators of their size and performance. Although such data has already been published for many years, the experience recently g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 14 publications
(12 reference statements)
1
19
1
Order By: Relevance
“…This agrees with cost equations that came from studies at the CERN-LHC in 1999 [9,10]. The largest plants shown in FIGURE 2 are quite complex.…”
Section: Large 45 K Helium Refrigerator Capital Costsupporting
confidence: 84%
“…This agrees with cost equations that came from studies at the CERN-LHC in 1999 [9,10]. The largest plants shown in FIGURE 2 are quite complex.…”
Section: Large 45 K Helium Refrigerator Capital Costsupporting
confidence: 84%
“…Models for the cost of cryogenic refrigeration systems have been developed and updated over the years [61,62,63,64,65,58]. These models were based on the actual costs to purchase cryogenic refrigeration systems operating between 4.2 K and 80 K. In order to fairly compare these systems, actual costs were adjusted to a reference refrigeration system.…”
Section: Cryogenic Systemsmentioning
confidence: 99%
“…B LHC studies with cryogenic industry has shown that a 24 kW (4.5K equivalent) sized plant is the largest for which the LHC Project Report 317 [58] design methodology is applicable.…”
mentioning
confidence: 99%
“…To cope with its heat loads, the LHC will require eight large helium cryogenic plants, each producing a mixed duty of liquefaction and refrigeration at different temperatures, with an equivalent capacity of 18 kW @ 4.5 K and a coefficient of performance (c.o.p.) of 230 W/W [19]. The coldbox of the first LHC cryogenic plant, presently undergoing reception tests at CERN, is shown in FIGURE 9.…”
Section: Superfluid Helium Cryogenicsmentioning
confidence: 99%